(untitled) (Journal of Global Accounting, 2024)
This study investigated the effect of audit quality on the financial performance of listed consumer goods firms in Nigeria. The specific objectives of the study are to examined; the effect of auditor’s independence, audit firm size and audit fees on return on assets of listed consumer goods firms. Ex- post facto research design was adopted for the study. Purposive sampling technique was used to select examine from the 19 listed consumer goods firms in Nigeria. The study relied on secondary data obtained from audited annual reports and accounts of the selected firms. Ordinary Least Squares regression method was used in the analysis of data. The study finds out that audit firm size has a positive and significant effect on financial performance of listed consumer goods firms, audit fees has a negative and significant effect on financial performance of listed consumer goods firms, among others was concluded that audit firm size influence financial performance of consumer goods firms in Nigeria. We therefore recommend that management of consumer goods firms should employ the services of one of the Big 4 audit firms, management should go for an audit firm whose character and integrity is beyond question in order to enhance financial performance of consumer goods firms.